Cryopreserved placental biopsies maintain mitochondrial activity for high-resolution respirometry - Matteo Giovarelli; Anais Serati; Silvia Zecchini; Fabiola Guelfi; Emilio Clementi; Chiara Mandò (BMC, 2023)
Abstract Background High-resolution respirometry (HRR) of human biopsies can provide useful metabolic, diagnostic, and mechanistic insights for clinical research and comparative medical studies. Fresh tissues analysis offers the potential best condition, the drawback being the need to use them shortly after dissection for mitochondrial respiratory experiments. The development of effective long-term storage protocols for biopsies that allow the assessment of key Electron Transport System (ETS) parameters at later stages is thus a major need. Methods We optimised a cryopreservation protocol that preserves mitochondrial membranes intactness, otherwise affected by direct tissue freezing. The protocol is based on a gradual freezing step from on-ice to liquid nitrogen and − 80 °C storage using a specific DMSO-based buffer. Results Placenta is a suitable tissue to design and test the effectiveness of long-term storage protocols being metabolically active foetal tissue with mitochondrial dysfunctions contributing to placental disease and gestational disorders. Here we designed and tested the effectiveness of the cryopreservation protocol using human placenta biopsies; we measured the ETS activity by HRR of placenta specimens comparing fresh, cryopreserved, and snap frozen conditions. Conclusions By this protocol, Oxygen Consumption Rate (OCR) measurements of fresh and cryopreserved placental specimens are comparable whereas snap frozen procedure impairs mitochondrial activity. Graphical Abstract